Transcriptomics Reveal Molecular Signatures of a Resolved Sexual Conflict and Potential Association With Colour Polymorphism in Tawny Owls - Baltazar-Soares, Miguel; Heckwolf, Melanie J.; Hoeppner, Marc P.; Karell, Patrik; Wright, Dominic; Nilsson, Jan-Åke; Brommer, Jon E. (Wiley, 2026)
Genome sharing in gonochorous species is expected to result in intraspecific conflicts due to intersexual competition. The emergence of sexual dimorphism is thus connected to the evolution of mechanisms that, starting from a similar genomic background, produce sufficiently disparate phenotypes to attenuate sexually antagonistic selection. From a molecular perspective it can be achieved through sex-specific differences in gene expression, splicing, non-coding regulation or epigenetic marks. The tawny owl (Strix aluco) is a sexually dimorphic species where females and males evolved distinct body sizes (smaller males), which results in sex-specific roles and therefore is a robust example of resolved sexual conflict. Here, we explore transcriptional variation among 32 juvenile tawny owls with the objective of investigating molecular signatures of resolved sexual conflict. Our results show substantial sex-specific variation in terms of differentially expressed genes, single nucleotide polymorphisms and alternative exon usage in genes involved in life history traits (ZGRF1, VLDLR), behaviour (GSK3B, SLC12A) and aspects of growth (GHR, EGF, EPS8L2). Exploring sex-specific DEG revealed enrichment for biological functions associated with melanogenesis and pigment granulation in males, which together with the identification of a single up-regulated autosomal gene involved in melanogenesis (RAB38) in brown males strongly suggests different timings for the onset of pigmentation between sexes. Overall, our results reveal some of the sex-specific molecular signatures expected to be observed in the context of a resolved sexual conflict.